Vulnerable mothers' experiences breastfeeding with an enhanced community lactation support program. Issue 3 (26th January 2020) - Francis, Jane; Mildon, Alison; Stewart, Stacia; Underhill, Bronwyn; Tarasuk, Valerie; Di Ruggiero, Erica; Sellen, Daniel; O'Connor, Deborah L.
Abstract: The Canada Prenatal Nutrition Program (CPNP) provides a variety of health and nutrition supports to vulnerable mothers and strongly promotes breastfeeding but does not have a formal framework for postnatal lactation support. Breastfeeding duration and exclusivity rates in Canada fall well below global recommendations, particularly among socially and economically vulnerable women. We aimed to explore CPNP participant experiences with breastfeeding and with a novel community lactation support program in Toronto, Canada that included access to certified lactation consultants and an electric breast pump, if needed. Four semistructured focus groups and 21 individual interviews ( n = 46 women) were conducted between September and December 2017. Data were analysed using inductive thematic analysis. Study participants reported a strong desire to breastfeed but a lack of preparation for breastfeeding‐associated challenges. Three main challenges were identified by study participants: physical (e.g., pain and low milk supply), practical (e.g., cost of breastfeeding support and maternal time pressures), and breastfeeding self‐efficacy (e.g., concern about milk supply and conflicting information). Mothers reported that the free lactation support helped to address breastfeeding challenges. In their view, the key element of success with the new program was the in‐home visit by the lactation consultant, who was highly skilled and provided care in a non‐judgmental manner. They reported this support would have been otherwise unavailable due to cost or travel logistics. This study suggests value in exploring the addition of postnatal lactation support to the well‐established national CPNP as a means to improve breastfeeding duration and exclusivity among vulnerable women.